FRECUENCIA DE Dirofilaria immitis EN CANINOS DEL DISTRITO DE SAN JUAN DE LURIGANCHO - Corimanya P., Jésica (2004)
Canid filariasis, known as Heartworm disease, is caused by a nematode named Dirofilaria immitis, which is located in the canid´s heart producing a cardiopulmonary disease and affecting others organs like liver and kidneys. Culex, Aedes and Anopheles female flies are the intermediary hosts. The objective of this study was to determine the prevalence of D. immitis in the San Juan de Lurigancho district, close to the Rímac river. Blood samples were taken from 107 dogs in apparently good health condition from May to June 2002. Animals were randomly chosen without regard of breed and sex, and were older than 6 months old. An enzimatic commercial ELISA test (Dirochek, Synbiotic®) was used. Six positive dogs were detected, representing a frequency of 5.5±4.7% with a 95% confidence interval. No differences due to sex and environment exposition were found. In conclusion, the frequency of dirofilariasis in canids of this district is low and similar to previous studies conducted in various districts of Lima.